PENGARUH KEMUDAHAN PENGGUNAAN, NILAI TIDAK TERGANTIKAN, KUALITAS SISTEM, KESADARAN TEKNOLOGI DAN DESAIN VISUAL TERHADAP POSITIF WORD OF MOUTH DAN NIAT PEMBELIAN ULANG DENGAN MEDIASI LOYALITAS MEREK - Ali Wardhana; Yulia Yulia (Unib Press Universitas Bengkulu, 2020)
Nowadays smartphones have become a necessity, so policy makers need to understand usage, irreplaceable value, system quality, technological awareness and visual design of repurchase commitments and positive word of mouth with mediating brand loyalty. By knowing the impact, companies, especially those who are increasing growth slowdown can use it to acquire new consumers and also increase repurchases. The results showed that only 2 variables could be used to increase positive word of mouth and repurchase goals mediated by brand loyalty, namely system quality and technological awareness. This study also shows that the use and value that is irreplaceable is considered irrelevant in increasing brand loyalty considering that smartphones have become a widely used product every day with a variety of products that are marketed.Keyword: System Quality ; technology consciousness; brand loyalty ; repurchase intention ; positive WOM